The influence of academic and social factors on degree attainment in BSc Sport and Exercise Science - Hastings, Jayne (2022)
Although admissions procedures vary between universities, applicants’ prior attainment is the main criteria used to decide whether to make an offer or accept an applicant onto a course. Widening participation has meant that students entering higher education are now coming from a wider range of backgrounds than before and with more diverse social, economic, and educational backgrounds. However, there is limited research on the intersecting effects of qualification type, social class, gender, and ethnicity on degree attainment. Using a mixed methods study design, and informed by Bourdieu’s theory of practice, this research goes further than many others who have considered qualification outcomes to identify a range of academic and social factors that influence degree attainment in Sport and Exercise Science within a post-1992 university. The quantitative aspect of the research comprises statistical analysis of a five-year cohort of students who enrolled onto the course between 2011/12 and 2015/16 and used predominantly non-parametric statistics of categorical data. Multinomial logistic regression is used to model the relationship between the academic and social factors investigated (predictors) and degree outcomes. The academic factors, UCAS Tariff points (Tariff from 3) and Level 3 qualification, are the strongest predictors of degree outcomes and were included in the final regression model. The social factors gender and ethnicity were also included. Socio-economic class has a limited effect on attainment when other factors are taken into account and was not included in the final model. The regression model predicts better degree outcomes for those with a higher UCAS Tariff from 3, studied A-Levels, were female, and white. BTEC students were more likely to be BME, male, and from a lower POLAR4 quintile and therefore represent some of the intersectionality of factors that contribute to differential degree outcomes. Based on the analysis of in-depth interviews with nine year two students on the course in 2019, the intersectionality of the participants backgrounds, qualification routes, genders and ethnicities was investigated to see how this may have impacted on their educational trajectories. There are no simple explanations as to the reasons for the differential degree attainment of A-Level and BTEC students. The challenges and concerns highlighted by students on the course around perceived lack of support, independent study, and different teaching, learning and assessment types could be explained by a ‘mismatch’ between their own cultural capital and habitus and the university field that they have entered. However, it was hard to attribute any learning and assessment preferences firmly to a particular qualification type. The data suggests that the institutionalised cultural capital and habitus of 6th form colleges may be better aligned to university than that of FE colleges, facilitating better transitions and ultimately resulting in better degree outcomes. The dispositions and habitus of females may be better aligned to the university field and the study habits required for academic success and therefore may have contributed to the reason why females do better than males on the course.